2001
DOI: 10.1088/0022-3727/34/18/321
|View full text |Cite
|
Sign up to set email alerts
|

Study of the structure and deviation from equilibrium in direct current supersonic plasma jets

Abstract: Mathematical modelling and optical emission spectroscopy are applied to study the effect of the chamber pressure on the structure and properties of supersonic plasma jets formed by a direct current arc. In this installation the plasma is created inside the nozzle where the flow is accelerated. As a result some deviation from thermal and ionization equilibrium can be found, even at the working chamber inlet. In this paper, by means of a two-temperature model, we study the argon jet flow using the data of the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 26 publications
6
44
0
Order By: Relevance
“…This may result in the strong drop of the heavy particle temperature in the expansion region with respect to the temperature of free electrons. On the other hand, in the shock region, the heavy particle temperature may even exceed the electron temperature [31,32]. From the present results and from the assumption that the populations of excited species can be in partial equilibrium with free electrons, we suppose the temperature we have obtained may be close to the temperature of free electrons.…”
Section: Resultssupporting
confidence: 55%
“…This may result in the strong drop of the heavy particle temperature in the expansion region with respect to the temperature of free electrons. On the other hand, in the shock region, the heavy particle temperature may even exceed the electron temperature [31,32]. From the present results and from the assumption that the populations of excited species can be in partial equilibrium with free electrons, we suppose the temperature we have obtained may be close to the temperature of free electrons.…”
Section: Resultssupporting
confidence: 55%
“…The RNG k-ε model has been proved to provide accurate and reliable results for a wide class of flows with high Reynolds number and pressure gradient, particularly for internal nozzle flows [4,[6][7][8][9]. In addition, Zhu et al [10] showed that the RNG k-ε model provided flow fields for the system configuration and Mach number similar to those of this study, in better agreement with experiments than any other turbulence model.…”
Section: Governing Equationssupporting
confidence: 75%
“…In the plasma jet, the plasma is formed and accelerated at the same time and the collision process cannot establish thermal and ionization equilibrium [39]. Our work proves that excitation equilibrium cannot establish, either.…”
Section: Resultsmentioning
confidence: 64%